Fatigue behavior of steel fiber reinforced geopolymer concrete. (June 2022) - da Silva, Alisson Clay Rios; Almeida, Bianca Mendes; Lucas, Mathaus Moraes; Cândido, Verônica Scarpini; da Cruz, Kamila Sindy Pinheiro; Oliveira, Michelle Souza; de Azevedo, Afonso Rangel Garcez; Monteiro, Sergio Neves
Abstract: Geopolymer concrete (GCC) is a high-performance concrete, where a geopolymer mass serves to bond coarse aggregates, steel fiber and any non-reactive materials. The development of this concrete is an important step for the production of ecologically correct concrete. Indeed, in addition to reducing CO2, a common fact in cement industries, it also uses waste. The fatigue behavior of GCC reinforced with steel fiber was evaluated by dynamically cycled tensile tests and compared with ordinary Portland concrete (OPCC). In both types of concrete, the effects of different cement aging time (1, 7 and 28 days) and ratio of minimum applied stress level (R = σmin / σflex ) with quasi-static flexural strength (0.07, 0.20 and 0.40) as well as the volume fraction of added steel fiber (0.5 and 1.0 vol%) were disclosed. The GCC fatigue resistance associated with the number of cycle to rupture was, in average, higher than that of OPCC and, in particular 96% superior after 7 days of aging. As for the minimum applied stress ratio, the results showed a better performance of the GCC with unchanged mean values 50% higher than those of OPCC. Regarding the addition of steel fibers, comparable values were found for both GCC and OPCC within the standard deviation. These values are significantly higher, more than 4 times, than those of unreinforced concretes. The GCC SEM fractographs revealed a better cement matrix interfacial adhesion with both aggregates and steel fibers, as compared with OPCC. This was attributed to fibrous crystalline phase formation at the GCC cement interfaces.